Effects of maternal supplementation of guanidinoacetic acid on skeletal muscle growth and metabolism in beef offspring - Kladt, Luiza V.; Costa, Thaís C.; Sousa, Luiz C. O.; Santos, Marta M.; Varizi, Jenifer K. C.; Rodrigues, Livia S.; Motta, Luiz J. M.; Silva, Walmir; Paulino, Pedro V. R.; Resende, Tales L.; Sampaio, Claudia B.; Gionbelli, Mateus P.; et al. (Frontiers in Animal Science, 2025)
Guanidinoacetic acid (GAA) is a precursor of creatine and is an arginine-sparing compound that may improve energy metabolism and muscle growth. Its potential in beef cow–calf systems, however, is still poorly understood. This study evaluated the effects of supplementing pregnant cows with GAA during late gestation on muscle development and adipogenesis in beef calves. A total of 24 pregnant Brahman cows carrying male or female fetuses received either a control diet or a diet supplemented with 0.2% GAA from day 180 to day 270 of gestation. Cows were weighed at the beginning and at the end of the trial to assess body weight (BW), and daily feed intake was recorded. Blood was collected on day 227 of gestation for plasma amino acid profiling, and the carcass traits were assessed via ultrasound. At 45 days of age, muscle biopsies were collected for mRNA expression and protein abundance. All statistical analyses were performed in SAS Studio using a mixed model including the fixed effects of treatment and offspring sex. In cows, GAA supplementation did not affect the BW, average daily gain, or feed intake (p > 0.05), but increased the plasma arginine, citrulline, and ornithine levels (p ≤ 0.02) and the final ribeye area (p = 0.01). The calves from GAA-supplemented cows exhibited increased p-Akt/Akt (p = 0.03) and p-mTOR/mTOR (p < 0.01) ratios, with treatment × sex interactions (p = 0.02). The MYOD1 mRNA expression was upregulated (p = 0.01), whereas MYOG remained unchanged (p = 0.14). The PAX7 protein tended to be higher (p = 0.07) and PAX3 reduced (p = 0.01) in GAA calves. No differences were detected for the adipogenic markers. These findings suggest that maternal GAA supplementation can stimulate muscle development in beef calves without altering intramuscular adipogenesis, indicating a potential strategy to enhance muscle growth programming in cow–calf production systems.